Identification of the gene network modules highly associated with the synthesis of phenolics compounds in barley by transcriptome and metabolome analysis. (1st September 2020) - Han, Zhigang; Ahsan, Muhammad; Adil, Muhammad Faheem; Chen, Xiaohui; Nazir, Muhammad Mudassir; Shamsi, Imran Haider; Zeng, Fanrong; Zhang, Guoping
Highlights: A total of 118 pheonlic metabolites are identified during grain developing stages. Phenolic metabolites are greatly affected by genotype and drought stress. Two significant modules are uncovered by network analysis of 17, 424 highly expressed genes. Five hub genes and transcription factor bHLH131 are involved in phenoic pathway. Abstract: Phenolic compounds in barley grains have an important influence on beer flavor and stability. Drought condition enhances the content of phenolics in barley grains, leading to reduced malt quality. In this study, two barley genotypes, XZ20 and XZ25 with different total phenolics content were used to investigate the effect of drought on phenolic compounds during grain developing stage. Totally, 118 phenolic metabolites were affected by drought stress. A weighted gene co-expression network analysis (WGCNA) of 17, 424 highly expressed genes uncovered black (two hub genes belonged to UGT family) and turquoise modules (three hub genes belonged to phenolics pathway) that are significantly associated with the variation of phenolics. All these results reveal the changes of phenolic metabolites during grain development and provide a new insight into the regulation network of phenolic compounds under drought stress.